Plural times and temporal modification - Artstein, Ron; Francez, Nissim (Proceedings of the Amsterdam Colloquium, 2003)
We propose a semantics with plural entities and plural times that accounts for cumulative relations between plural arguments and temporal expressions within a clause. The semantics equips nominal, verbal and sentential meanings with temporal context variable and treats temporal PPs and clauses as temporal generalized quantifiers [6,7]. The mediation of temporal context variables also allows cumulative relations to percolate between an argument in a main clause and one in a temporal clause, in apparent violation of locality restrictions. Plural times form a semilattice structure [5] imposed on the set of intervals; no interaction is observed between this and the internal temporal structure of intervals.